The Reality of Teaching Practices Consistent with the Principles of Brain-Based Learning among Middle School Science Teachers from the point of view of Educational Supervisors in the City of Tabuk - Dr. Nuha Mustafa Al-Obaidan (Journal of Arts, Literature, Humanities and Social Sciences, 2024)
The objective of the current research is to determine the reality of teaching practices consistent with the principles of brain-based learning of middle-stage science teachers from the point of view of the 12 educational supervisors in Tabuk, who represented and appointed the research community, using the survey descriptive curriculum. In order to achieve the research objectives, the researcher formulated the main question of the research as follows: What is the reality of teaching practices consistent with the principles of brain-based learning of female science teachers for the middle stage from the point of view of female pedagogical supervisors, and the main question is the sub-questions that determine the reality of teaching practices in four axes, including: lesson planning, lesson implementation, evaluation and educational environment, To answer research questions, the researcher applied research tools that represented a measure of teaching practices consistent with the principles of brain-based learning. The researcher used appropriate statistical methods to extract the results, and the results of the research resulted in, That the response of research personnel came at a level consistent with the realities of teaching practices consistent with the principles of brain-based learning of science teachers for the middle stage from the point of view of educational supervisors in the course planning axis with a computational average (2.63); The results showed that the research response was such that the reality of teaching practices consistent with the principles of brain-based learning in science teachers for the middle stage was accepted from the point of view of educational supervisors in the course's implementation axis with an average arithmetic (2.66). and that research personnel agree favourably with the realities of teaching practices consistent with the principles of brain-based learning of middle-level science teachers from the point of view of educational supervisors in the axis of evaluation methods with an average arithmetic (2.39), The response of research personnel was consistent with the reality of teaching practices consistent with the principles of brain-based learning of middle-level science teachers from the educational supervisors' point of view of the educational environment on average (2.47).